Synergistic combination of plants and microbial-rich substrates improves water quality in an integrated plant-substrate system - Sopawong, Arissara; Md Yusoff, Fatimah; Zakaria, Muta Harah; Amin, S.M. Nurul; Tan, Hui Teng; Mohd Hashim, Amalia (Asian Fisheries Society, 2023)
Nutrient enrichment is one of the main reasons causing water quality deterioration and eutrophication in aquaculture systems, such as tanks, ponds, and natural water bodies where cage aquaculture is located. The integration of aquatic plants and substrates synergistically utilises nutrients for the development of biofilm and plant growth, thus improving the water quality in tanks. The experiment was performed in three trials to assess the use of commercial plants integrated with substrates in enhancing nutrient removal in nutrient-enriched mesocosms. Among the plants, the combination of water spinach and lemon basil exhibited significantly higher (P < 0.05) nutrient removal without causing adverse effects on plant growth when compared to the other treatments. For the substrates, the lava rock and bamboo showed the highest (P < 0.05) periphyton development and productivity. The integration of water spinach and lava rock resulted in the highest (P < 0.05) nutrient removal and plant relative growth rates indicating the positive effects of synergistic interaction between plants and microbial-periphyton colonised substrates. A total of 27 bacterial phyla (mainly non-pathogenic) were identified in the integrated water spinach and lava rock substrate treatment. Microbial community structure analysis showed that Proteobacteria, Planctomycetota, Verrucomicrobiota and Bacteroidota were the main groups found in water, roots of water spinach, and substrates. The highest (P < 0.05) bacterial diversity was observed in the substrates, followed by plant roots and water. This study illustrated that the water quality could be significantly improved by integrating suitable plants and microbial-periphyton colonised substrates in tanks.